Algebraic graph theory : morphisms, monoids and matrices - Knauer, Ulrich, 1942-; Knauer, Kolja (Berlin ; Boston : De Gruyter, 2019)
The series is devoted to the publication of monographs and high-level textbooks in mathematics, mathematical methods and their applications. Apart from covering important areas of current interest, a major aim is to make topics of an interdisciplinary nature accessible to the non-specialist. The works in this series are addressed to advanced students and researchers in mathematics and theoretical physics. In addition, it can serve as a guide for lectures and seminars on a graduate level. The series de Gruyter Studies in Mathematics was founded ca. 30 years ago by the late Professor Heinz Bauer.
Directed and undirected graphs -- Graphs and matrices -- Categories and functors -- Binary graph operations -- Line graph and other unary graph operations -- Graphs and vector spaces -- Graphs, groups and monoids -- The characteristic polynomial of graphs -- Graphs and semigroups -- Compositions, unretractivities and monoids -- Cayley graphs of semigroups -- Vertex transitive Cayley graphs -- Embeddings of Cayley graphs : genus of semigroups.
Includes bibliographical references and indexes.
Online resource; title from PDF title page (publisher's Web site, viewed 22 Oct. 2019).
eBooks on EBSCOhost
Keywords: Graph theory; Algebraic topology; Topologie algébrique.; Algebraic topology; Graph theory